War and peace in the age of corona: an analysis of support for repressive state policies in divided societies. (15th March 2022) - Gurses, Mehmet; Balta, Evren; Çelik, Ayşe Betül
ABSTRACT: Unlike various natural disasters that some studies have highlighted as potential contributors to peace, the threat posed by the COVID-19 pandemic is neither short-term nor regionally confined. Thus, rather than invoking a compassionate response, the pandemic is likely to aggravate pre-existing divisions and create an environment that accentuates survival over compassion. Building on a large probability survey data gathered in May 2020 in Turkey, we demonstrate that the pandemic has disproportionally affected minority Kurds and exacerbated pre-existing inequalities and social polarization. Results from a series of regression analyses show growing dissatisfaction with the Turkish government's handling of the pandemic. However, this effect fails to translate into the sense of solidarity between majority Turks and minority Kurds necessary to build a peaceful society. Support for the government's approach to the Kurdish opposition seems to be conditioned by social categorization and increasingly partisan political identities in Turkey.